GEOPOLITICS OF FAITH AS A DEVICE OF POWER: RELIGIOUS INSTRUMENTALIZATION, CONFLICTS AND FORCED DISPLACEMENT IN THE CONTEMPORARY MIGRATION CRISIS - Vieira, Sofia Rumor Marin D´iglesias; Costa, Silvana Afonso; Palhares, José Mauro (Seven Editora, 2026)
This study analyzes the geopolitics of faith based on the understanding of religion as a device of power in contemporary dynamics, investigating its instrumentalization in the production of geopolitical conflicts, social exclusions, and forced displacement. Situated within the fields of social sciences and international relations, the study examines how religious discourses and practices are mobilized by state actors, political agents, and armed groups as mechanisms for legitimizing violence, social control, and territorial reorganization on a global scale, with emphasis on the Middle East. The objective is to understand the role of faith in the production of exclusion, conflicts, and migration crises, as well as to analyze its impacts on contemporary geopolitical dynamics. To this end, a qualitative, exploratory, and bibliographic approach is adopted, based on academic literature, reports from international organizations, and institutional documents. Thus, it is observed that, although religion holds potential for social cohesion and solidarity, it has frequently been instrumentalized as a justification for persecution, human rights violations, and the intensification of conflicts, contributing to large-scale migratory flows. The findings indicate that religious instrumentalization constitutes a transnational and multifaceted phenomenon, with direct impacts on the reconfiguration of international relations and the expansion of humanitarian crises, requiring coordinated responses involving diplomatic actions, public policies, and international cooperation aimed at promoting human rights and building scenarios of peace.